Suppression of NLRP3 Inflammasome by Erythropoietin via the EPOR/JAK2/STAT3 Pathway Contributes to Attenuation of Acute Lung Injury in Mice - Cao, Fei; Tian, Xinyi; Li, Zhongwang; Lv, Ya; Han, Jun; Zhuang, Rong; Cheng, Bihuan; Gong, Yuqiang; Ying, Binyu; Jin, Shengwei; Gao, Ye (Frontiers in Pharmacology, 2020)
Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are common and devastating clinical disorders with high mortality and no specific therapy. An excessive inflammatory response results in the progression of ALI/ARDS, and the NLRP3 inflammasome is a key participant in inflammation. Erythropoietin (EPO), which is clinically used for anemia, reportedly exerts pleiotropic effects in ALI. However, whether EPO could protect against lipopolysaccharide (LPS)-induced ALI by regulating the NLRP3 inflammasome and its underlying mechanisms remain poorly elucidated. This study aimed to explore whether the therapeutic effects of EPO rely on the suppression of the NLRP3 inflammasome and the specific mechanisms in an LPS-induced ALI mouse model. ALI was induced in C57BL/6 mice by intraperitoneal injection of LPS (15 mg/kg). EPO was administered intraperitoneally at 5 U/g after LPS challenge. The mice were sacrificed 8 hours later. Our findings indicated that application of EPO markedly diminished LPS-induced lung injury by restoring histopathological changes, lessened lung wet/dry ratio, protein concentrations in bronchoalveolar lavage fluid (BALF) and myeloperoxidase (MPO) levels. Meanwhile, EPO evidently decreased interleukin-1β (IL-1β) and IL-18 secretion, the expression of NLRP3 inflammasome components including pro-IL-1β, NLRP3 and Cleaved Caspase-1 as well as phosphorylation of NF-κB p65, which may be associated with activation of EPO receptor (EPOR), phosphorylation of JAK2 and STAT3. However, all the beneficial effects of EPO on ALI and modulation NLRP3 inflammasome were remarkably abrogated by the inhibition of EPOR/ JAK2/STAT3 pathway and knockout of NLRP3 gene. Taken together, this study indicates that EPO can effectively attenuate LPS-induced lung injury in mice by suppressing the NLRP3 inflammasome, which is dependent upon activation of EPOR/JAK2/STAT3 signaling and inhibition of the NF-κB pathway.